Determinants of Mutual Funds Performance in Pakistan - Asad, Muhammad; Siddiqui, Danish Ahmed (International Journal of Social and Administrative Sciences, 2019)
The aim of this thesis is to investigate various fund attributes influencing returns of Pakistani mutual funds. For this ten types of Mutual funds were selected for the period of 2015-17, and the effect of six micro and two macro fund specific variables on their returns were analyzed. Models have analyzed the effect of all factors in different categories of funds & for different classes of funds. Results showed that the attributes having impact on mutual fund return are risk and expense ratio positively. Some variables have no impact on fund returns i.e. fund size, fund age, and risk return coefficient, moreover macroeconomic factors (GDP and Interest rate) & risk adjusted return have negative relation on fund returns. Macro factors impact have difficult to analyzed with mutual fund return because relation of fund returns mostly depends on its micro factors and its fund manager expectation regarding market. However macro-economic factors affect the overall fund market or any specific class of funds. Sector wise analyze describes the detail effect of each variable in this research, however expense ratio have positive effect on fund return in conventional return but negative for Islamic fund returns.